On the Combined Action of Low-Intensity Physical Factors and Intensive Physical and Chemical Factors in Medicine - Boldyreva, Liudmila B. (Research Developments in Medicine and Medical Science Vol. 1, 2023)
Biological systems are normally highly sensitive to low-frequency, low-intensity electromagnetic fields. The possibility of successful treatment action on biological objects of intensive physical and chemical factors in conjunction with biologically active substances in ultra-low doses and with low-intensity physical factors is addressed. Low-intensity physical factors include infra-low-frequency magnetic fields, the field-free magnetic vector potential, the effect of cavity structures, and quantum correlation of quantum entities.